Double-metal cyanide catalyst, preparation method thereof and preparation method of low-carbon fatty alcohol polyether

By preparing a bimetallic cyanide catalyst, the problems of free alcohol residue and polyethylene glycol byproduct formation in the preparation of JFC from low-carbon alcohols were solved, and the efficient preparation of low-carbon alcohol polyethers at low temperatures was achieved, with excellent product performance.

CN121372477APending Publication Date: 2026-01-23CHINA ENERGY GRP NINGXIA COAL IND CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511296230.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-11
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

When existing strong alkaline catalysts are used to prepare JFC from low-carbon alcohols, the free alcohol residue is high during the reaction process, and the catalyst reacts with the initiator to generate water, resulting in more polyethylene glycol byproducts and a wider molecular weight distribution of polyether in the product.

Method used

A bimetallic cyanide catalyst preparation method was adopted, in which soluble transition metal salts, cyano metal salts, reaction media and dispersants were mixed and reacted under an inert atmosphere to prepare catalysts with cubic, plate or amorphous morphologies, which were then used to catalyze the alkoxylation reaction of fatty alcohols at a relatively low temperature.

Benefits of technology

It effectively reduces free alcohol residue, decreases the generation of polyethylene glycol byproducts, has a narrower molecular weight distribution, improves reaction conversion rate and selectivity, and the prepared low-carbon alcohol polyether has excellent penetration and emulsification properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005591648590000181
    Figure BDA0005591648590000181
  • Figure BDA0005591648590000191
    Figure BDA0005591648590000191
  • Figure BDA0005591648590000192
    Figure BDA0005591648590000192
Patent Text Reader

Abstract

The invention relates to the technical field of penetrant JFC preparation, and discloses a double-metal cyanide catalyst and a preparation method thereof, and a preparation method of low-carbon fatty alcohol polyether. The preparation method of the double-metal cyanide catalyst comprises the following steps: mixing soluble transition metal salt, cyano metal salt, a reaction medium and a dispersing agent, and then reacting in an inert atmosphere, wherein the cyano metal salt is K3 [M (CN) 6], and the metal M is selected from at least one of Co, Fe and Cr. The double metal cyanide catalyst can effectively reduce the temperature for synthesizing polyether from low-carbon alcohol, has high catalytic reaction activity, and can reduce free alcohol residues in the reaction process. Meanwhile, the catalyst does not react with the initiator to generate water, so that the generation of a polyethylene glycol byproduct can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of preparation of penetrant JFC, in particular to a double metal cyanide catalyst, a preparation method thereof and a preparation method of low-carbon fatty alcohol polyether. BACKGROUND

[0002] Penetrant (JFC) is a kind of non-ionic surfactant with excellent penetration performance, which is widely used in textile, printing and dyeing and leather industry. The conventional JFC penetrant is prepared by using C7-C10 fatty alcohol as raw material, and reacting with ethylene oxide under the catalysis of alkaline catalyst, and the average addition number of ethylene oxide is controlled in the range of 4-6. In recent years, with the improvement of comprehensive utilization level of coal resources, some low-carbon alcohols (C6-C8) from coal-based sources have also become important raw materials for preparing JFC.

[0003] At present, the catalysts for producing fatty alcohol polyether non-ionic surfactants on the market mainly adopt conventional strong alkaline catalysts such as KOH and NaOH, which are widely used for alkoxylation of raw materials such as fatty alcohols. The catalytic characteristics are high reaction safety and stable reaction, which can effectively complete the reaction. However, there are some problems in the preparation of JFC from coal-based low-carbon alcohol, such as incomplete reaction of raw material alcohol, high residual free alcohol in the reaction process, resulting in high free alcohol content in the product; the strong alkaline catalyst generates water, resulting in high content of polyethylene glycol by-product in the product; and the molecular weight distribution of the product polyether is wide. SUMMARY

[0004] The present application aims to overcome the problems in the prior art, such as high residual free alcohol in the reaction process when using strong alkaline catalyst to prepare JFC from low-carbon alcohol; the catalyst reacts with initiator to generate water, resulting in more polyethylene glycol by-products; and the molecular weight distribution of the product polyether is wide. A double metal cyanide (DMC) catalyst and a preparation method thereof and a preparation method of low-carbon fatty alcohol polyether are provided, which can effectively reduce the synthesis temperature of polyether, and the catalyst has high catalytic activity, which can reduce the residual free alcohol in the reaction process. At the same time, since such catalyst does not react with initiator to generate water, the generation of polyethylene glycol by-products can be reduced.

[0005] In order to achieve the above-mentioned purpose, the present application provides a preparation method of double metal cyanide catalyst, which comprises: mixing soluble transition metal salt, cyanide metal salt, reaction medium and dispersant, and then reacting under inert atmosphere; wherein the cyanide metal salt is K3[M(CN)6], wherein the metal M is selected from at least one of Co, Fe and Cr.

[0006] Optionally, the soluble transition metal salt is a zinc salt and / or a nickel salt, preferably at least one of zinc chloride, zinc sulfate and nickel chloride.

[0007] Optionally, the molar ratio of the amount of the soluble transition metal salt to the amount of the cyanometal salt is (1.0-10):1, wherein the soluble transition metal salt is calculated based on transition metal element and the cyanometal salt is calculated based on metal M element.

[0008] Optionally, when metal M is Co, the molar ratio of the amount of the soluble transition metal salt to the amount of the cyanometal salt is (1.5-10):1, preferably (5.5-6.1):1, wherein the soluble transition metal salt is calculated based on transition metal element and the cyanometal salt is calculated based on metal Co element.

[0009] Optionally, when metal M is Fe, the molar ratio of the amount of the soluble transition metal salt to the amount of the cyanometal salt is (1.5-2.5):1, preferably (1.8-2.2):1, wherein the soluble transition metal salt is calculated based on transition metal element and the cyanometal salt is calculated based on metal Fe element.

[0010] Optionally, when metal M is Cr, the molar ratio of the amount of the soluble transition metal salt to the amount of the cyanometal salt is (1.0-3.5):1, preferably (2.1-3.2):1, wherein the soluble transition metal salt is calculated based on transition metal element and the cyanometal salt is calculated based on metal Cr element.

[0011] Optionally, the reaction medium is selected from at least one of borate ester compounds, cage polydentate ligands, polyionic liquids and chiral bis-Salen ligands, preferably at least one of phenyl boronic acid polyether ester, adamantane polycarboxylic acid, polyvinylimidazole and cis-norbornene bridged Salen-Ti.

[0012] Optionally, the amount of the reaction medium is 10-30wt%, preferably 15-25wt% of the mass of the soluble transition metal salt.

[0013] Optionally, the dispersant is selected from at least one of polyethylene glycol, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, polytetrahydrofuran, 18-crown-6 ether and comb copolymer DSP.

[0014] Optionally, the amount of the dispersant is 0.5-5wt%, preferably 3-5wt% of the mass of the soluble transition metal salt.

[0015] Optionally, the reaction conditions include that the reaction temperature is 35-105℃, preferably 50-80℃, and the reaction time is 0.5-24h, preferably 1.5-2h.

[0016] Optionally, the method further comprises, after the reaction is carried out under the inert atmosphere, standing, filtering the obtained precursor slurry, and washing and drying the obtained solid product.

[0017] The second aspect of the present application provides a double metal cyanide catalyst prepared by the method described above.

[0018] The third aspect of the present application provides a method for preparing a low-carbon fatty alcohol polyether, which comprises: reacting a low-carbon fatty alcohol initiator, a double metal cyanide catalyst, a cocatalyst, and an alkylene oxide.

[0019] The low-carbon fatty alcohol initiator has 6-10 carbon atoms.

[0020] The double metal cyanide catalyst is a double metal cyanide catalyst prepared by the method described above or the double metal cyanide catalyst described above.

[0021] Optionally, the low-carbon fatty alcohol initiator is a saturated alkane with 6-8 carbon atoms.

[0022] Optionally, the cocatalyst is selected from at least one of KOH, NaOH, NaHCO3, and Na2CO3.

[0023] Optionally, the alkylene oxide is ethylene oxide and / or 1,2-propylene oxide.

[0024] Optionally, the content of the double metal cyanide catalyst is 20-100 ppm, preferably 20-50 ppm, based on the total weight of the low-carbon fatty alcohol initiator and the double metal cyanide catalyst.

[0025] Optionally, the amount of the cocatalyst is 5-20 wt%, preferably 8-15 wt%, of the mass of the double metal cyanide catalyst.

[0026] Optionally, the mass ratio of the alkylene oxide to the low-carbon fatty alcohol initiator is (1.1-2.7):1.

[0027] Optionally, the process of reacting the low-carbon fatty alcohol initiator, the double metal cyanide catalyst, the cocatalyst, and the alkylene oxide comprises: mixing the low-carbon fatty alcohol initiator, the double metal cyanide catalyst, and the cocatalyst, then adding part of the alkylene oxide for an induction reaction, and then adding the remaining part of the alkylene oxide for a subsequent reaction.

[0028] Optionally, the temperature of the induction reaction is 8-12℃ lower than the temperature of the subsequent reaction.

[0029] Optionally, the temperature of the induction reaction is 60-110℃, preferably 80-100℃; the temperature of the subsequent reaction is 70-115℃.

[0030] Optionally, the initial system pressure of the induction reaction is 0.05-0.2MPa; the induction reaction ends when the system pressure is lower than 0.05MPa.

[0031] Optionally, the system pressure is kept ≤0.3MPa during the addition of the remaining portion of alkylene oxide; the subsequent reaction ends when the system pressure is ≤0.03MPa after the addition of the remaining portion of alkylene oxide and the system pressure remains unchanged within 30min.

[0032] Optionally, the mass of the portion of alkylene oxide added in the induction reaction stage is 2-10wt% of the total mass of alkylene oxide.

[0033] Compared with the prior art, the present application has at least the following beneficial effects:

[0034] (1) The inventor of the present application found that, due to the small molecular weight and low boiling point of C6-C8 low-carbon alcohol, the conventional alkoxylization reaction conditions of 120-140℃ cannot achieve ideal results in the pretreatment dehydration stage and the reaction process when low-carbon alcohol is used to synthesize low-carbon fatty alcohol block / random polyether, the free alcohol content in the product is high, the molecular weight distribution of the product polyether is wide, and the content of polyethylene glycol byproduct is high, etc. Therefore, the inventor prepared a double metal cyanide catalyst by using a new method. The double metal cyanide catalyst can not only synthesize low-carbon alcohol block / random polyether at a lower reaction temperature, but also has high catalytic reaction activity, which can reduce the free alcohol residue in the reaction process; at the same time, since the catalyst does not react with the initiator to generate water, the generation of polyethylene glycol byproduct can be reduced, the molecular weight distribution of the product is narrow, the reaction difficulty is reduced, the waste of raw materials is avoided, and the conversion rate and selectivity of the reaction are improved. The process for preparing low-carbon alcohol block / random polyether of the present application is simple in operation, the prepared catalyst can present cubic, flaky or amorphous morphology, has a crystallinity of 50-80%, has high catalytic activity, and can catalyze the fatty alcohol alkoxylization reaction at a lower reaction temperature.

[0035] (2) The double metal cyanide catalyst prepared by the present application is used to synthesize low-carbon alcohol block / random polyether, the product has lower free alcohol content and polyethylene glycol content than the commercially available JFC product, and has higher permeability and cloud point, and has excellent permeability and emulsification properties. DETAILED DESCRIPTION

[0036] The specific embodiments of the present application are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0037] The endpoints of the ranges and any values disclosed herein are not limited to the precise values recited as the exact dimensions are not critical to the invention. Any numeric range recited is intended to include all values from the lower value to the upper value, inclusive of both values, and to also include any value approximately or roughly between the lower value and the upper value. Numeric ranges can be expressed as "from X to Y," where X and Y are numbers. The range can also be expressed as "from X to Y," where X is a number and Y is infinity. The range can also be expressed as "from X to Y," where X is a number and Y is not specified. In such cases, the range includes all values upwards of X, unless a specific format is recited, such as "from X upwards," or "from X upwards of Y," where Y is another number. Numeric ranges can be expressed as "from X to Y," where X is a number and Y is a number. The range can also be expressed as "from X to Y," where X is a number and Y is infinity. The range can also be expressed as "from X to Y," where X is a number and Y is not specified. In such cases, the range includes all values upwards of X, unless a specific format is recited, such as "from X upwards," or "from X upwards of Y," where Y is another number.

[0038] The present application provides a method for preparing a double metal cyanide catalyst, comprising: mixing a soluble transition metal salt, a cyanometal salt, a reaction medium and a dispersant, and then reacting under an inert atmosphere.

[0039] In the process of preparing a double metal cyanide catalyst, the present application can prepare a double metal cyanide catalyst by reacting (complexing reaction) two specific metal salts in the presence of a reaction medium and a dispersant, and the prepared catalyst can present a cubic, flaky or amorphous morphology, a crystallinity of 50-80%, and a high catalytic activity, and can catalyze the alkoxylation of fatty alcohols at a low reaction temperature.

[0040] In the present application, due to the presence of the dispersant, the soluble transition metal salt and the cyanometal salt can be more uniformly dispersed in the reaction medium, so that a double metal cyanide catalyst with better crystal form and higher reactivity can be obtained.

[0041] In a more specific embodiment, the process of mixing the soluble transition metal salt, the cyanometal salt, the reaction medium and the dispersant comprises: adding the soluble transition metal salt and the cyanometal salt into deionized water to form an aqueous solution, and then sequentially adding the reaction medium and the dispersant for mixing. By using this method for mixing, the uniformity of the dispersion of the soluble transition metal salt and the cyanometal salt in the mixing process can be further improved.

[0042] In some embodiments, the soluble transition metal salt is a zinc salt and / or a nickel salt, preferably at least one of zinc chloride, zinc sulfate and nickel chloride. Preferably, the soluble transition metal salt is preferably zinc chloride and / or nickel chloride; when zinc chloride and / or nickel chloride is used as the transition metal salt, the comprehensive effect of the prepared double metal cyanide catalyst for synthesizing low-carbon alcohol block polyether or low-carbon alcohol random polyether is further improved.

[0043] In some embodiments, the cyanometallic salt contains both K and M elements, and has a chemical formula of K3[M(CN)6], wherein the metal M is selected from at least one of Co, Fe and Cr. Preferably, the metal M is Co or Fe; when the M in the cyanometallic salt is Co or Fe, the comprehensive effect of the prepared double-metal cyanide catalyst for synthesizing low-carbon alcohol block polyether or low-carbon alcohol random polyether is further improved.

[0044] In the present application, by limiting the use amount ratio of the soluble transition metal salt to the cyanometallic salt in a specific range, the formed catalyst crystal form is more regular, which is beneficial to improve the catalytic activity of the catalyst.

[0045] In some embodiments, the molar ratio of the use amount of the soluble transition metal salt to the cyanometallic salt is (1.0-10):1, wherein the soluble transition metal salt is calculated based on the transition metal element, and the cyanometallic salt is calculated based on the metal M element.

[0046] Preferably, when the metal M is Co, the molar ratio of the use amount of the soluble transition metal salt to the cyanometallic salt is (1.5-10):1, preferably (5.5-6.1):1, wherein the soluble transition metal salt is calculated based on the transition metal element, and the cyanometallic salt is calculated based on the metal Co element.

[0047] Preferably, when the metal M is Fe, the molar ratio of the use amount of the soluble transition metal salt to the cyanometallic salt is (1.5-2.5):1, preferably (1.8-2.2):1, wherein the soluble transition metal salt is calculated based on the transition metal element, and the cyanometallic salt is calculated based on the metal Fe element.

[0048] Preferably, when the metal M is Cr, the molar ratio of the use amount of the soluble transition metal salt to the cyanometallic salt is (1.0-3.5):1, preferably (2.1-3.2):1, wherein the soluble transition metal salt is calculated based on the transition metal element, and the cyanometallic salt is calculated based on the metal Cr element.

[0049] In the present application, the reaction medium is selected from at least one of borate ester compounds, cage polydentate ligands, polyionic liquids and chiral bis-Salen ligands. Specifically, the borate ester compounds can be phenyl boronic acid polyether ester, the cage polydentate ligands can be adamantane polycarboxylic acid, the polyionic liquid can be polyvinylimidazole, and the chiral bis-Salen ligand can be cis-norbornene bridged Salen-Ti. In some embodiments, the reaction medium is used in an amount of 10-30 wt% of the mass of the soluble transition metal salt, preferably 15-25 wt%. The use of these compounds as reaction media and the control of the amount of reaction medium in this range can promote the dispersion efficiency of the raw materials and ensure the stability during the preparation of the catalyst.

[0050] In the present application, the dispersant can be selected from at least one of polyethylene glycol (PEG-4000), polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), polytetrahydrofuran (PTMEG), 18-crown-6 ether and comb copolymer DSP. Further, the dispersant can be used in an amount of 0.5-5 wt% of the mass of the soluble transition metal salt, preferably 3-5 wt%. Due to the presence of the dispersant, the soluble transition metal salt and the cyanometal salt can be more uniformly dispersed in the reaction medium, thereby obtaining a double metal cyanide catalyst with better crystal form and higher reactivity.

[0051] In the present application, the reaction conditions include a reaction temperature of 35-105℃, preferably 50-80℃, and a reaction time of 0.5-24h, preferably 1.5-2h. By limiting the temperature and time of the reaction within the preferred range, the double metal cyanide catalyst prepared is used to synthesize low-carbon alcohol block polyether or low-carbon alcohol random polyether with less by-products and a narrower molecular weight distribution, thereby further improving the overall effect in terms of wetting and permeation.

[0052] Further, the method further comprises: after the reaction is carried out under an inert atmosphere, standing, filtering the obtained precursor slurry, and washing and drying the obtained solid product. By standing, the reaction product can be layered, and by subsequent filtering, washing the solid product and drying, a purer product can be obtained.

[0053] The solvent used to wash the solid product includes water and an organic solvent, which can be tert-butyl alcohol and / or imidazole-based ionic liquid, preferably tert-butyl alcohol. The drying temperature is 25-85℃, preferably 60℃.

[0054] The double metal cyanide catalyst prepared by the method of the present application is used for synthesizing low carbon alcohol block polyether or low carbon alcohol random polyether, and can not only perform the reaction at a lower reaction temperature, but also has higher catalytic reaction activity, and can reduce free alcohol residues in the reaction process; meanwhile, since the catalyst does not react with the initiator to generate water, the generation of polyethylene glycol by-products can be reduced, the reaction difficulty is reduced, the waste of raw materials is avoided, and the conversion rate and selectivity of the reaction are improved.

[0055] The second aspect of the present application provides a double metal cyanide catalyst prepared by the method described above. The double metal cyanide catalyst of the present application is particularly suitable for preparing low carbon fatty alcohol block polyether or low carbon fatty alcohol random polyether. The catalyst can have a cubic, flaky or amorphous morphology, a crystallinity of 50-80%, and higher catalytic activity, and can catalyze the fatty alcohol alkoxylation reaction at a lower reaction temperature.

[0056] The third aspect of the present application provides a method for preparing low carbon fatty alcohol polyether, which comprises: reacting a low carbon fatty alcohol initiator, a double metal cyanide catalyst, a cocatalyst and an alkylene oxide.

[0057] The number of carbon atoms in the low carbon fatty alcohol initiator is 6-10;

[0058] The double metal cyanide catalyst is the double metal cyanide catalyst prepared by the method described above or the double metal cyanide catalyst described above.

[0059] In the process of preparing low carbon fatty alcohol polyether, the present application uses a saturated alkyl alcohol with a carbon atom number of 6-10, preferably 6-8, as a low carbon fatty alcohol initiator, and cooperates with the double metal cyanide catalyst prepared by the method described above, so that the reaction can be performed at a lower temperature.

[0060] Further, the low carbon fatty alcohol initiator can be a straight-chain saturated alkyl alcohol and / or a branched-chain saturated alkyl alcohol; when the low carbon fatty alcohol initiator is a mixture of straight-chain saturated alkyl alcohol and branched-chain saturated alkyl alcohol, the number of carbon atoms of the straight-chain saturated alkyl alcohol and the branched-chain saturated alkyl alcohol is the same, i.e. the low carbon fatty alcohol initiator of the present application uses a saturated alkyl alcohol with a single carbon atom number, which can better achieve the technical effects of the present application.

[0061] In the present application, the double metal cyanide catalyst and the cocatalyst are cooperated, which can further improve the conversion rate of fatty alcohol and improve the reaction activity. In some embodiments, the cocatalyst is selected from at least one of KOH, NaOH, NaHCO3 and Na2CO3.

[0062] In some embodiments, the alkylene oxide is ethylene oxide and / or 1,2-propylene oxide, preferably ethylene oxide and 1,2-propylene oxide. When the alkylene oxide is ethylene oxide and 1,2-propylene oxide, the weight ratio of the total amount of ethylene oxide to 1,2-propylene oxide is 1:0.2-0.55.

[0063] In some embodiments, the content of the double metal cyanide catalyst is 20-100 ppm based on the total weight of the low-carbon fatty alcohol initiator and the double metal cyanide catalyst; to further improve the conversion rate and selectivity of the reaction, preferably, the content of the double metal cyanide catalyst is 20-50 ppm based on the total weight of the mixture of the low-carbon fatty alcohol initiator and the double metal cyanide catalyst.

[0064] In some embodiments, the amount of the promoter is 5-20 wt% of the mass of the double metal cyanide catalyst; to further improve the conversion rate of the fatty alcohol, the amount of the promoter is 8-15 wt% of the mass of the double metal cyanide catalyst.

[0065] In the present application, to adjust the hydrophilic-lipophilic balance of the product, the mass ratio of the alkylene oxide to the low-carbon fatty alcohol initiator is (1.1-2.7):1.

[0066] In some embodiments, the process of the reaction of the low-carbon fatty alcohol initiator, the double metal cyanide catalyst, the promoter and the alkylene oxide comprises: mixing the low-carbon fatty alcohol initiator, the double metal cyanide catalyst and the promoter, then adding part of the alkylene oxide to induce the reaction, and then adding the remaining part of the alkylene oxide to carry out the subsequent reaction. Further, the temperature of the induction reaction is 8-12℃ lower than the temperature of the subsequent reaction.

[0067] In the present application, the temperature of the reaction is low, which reduces the difficulty of the reaction. Specifically, the temperature of the induction reaction is 60-110℃, preferably 80-100℃; the temperature of the subsequent reaction is 70-115℃.

[0068] In some embodiments, the initial system pressure of the induction reaction is 0.05-0.2 MPa; the induction reaction ends when the system pressure is lower than 0.05 MPa. After the induction reaction ends, the system pressure is kept ≤0.3 MPa during the period from the start of the addition of the remaining portion of the alkylene oxide to the completion of the addition of the remaining portion of the alkylene oxide; after the addition of the remaining portion of the alkylene oxide, the subsequent reaction ends when the system pressure is ≤0.03 MPa and the system pressure remains unchanged for 30 min. In the reaction process of the present application, the system pressure is controlled in this way, which can ensure the full reaction of the added alkylene oxide raw material and avoid the residual of the remaining unreacted alkylene oxide raw material.

[0069] In preferred embodiments, in order to quickly and safely initiate the addition reaction of the alkylene oxide, the mass of the portion of the alkylene oxide added in the induction reaction stage can be 2-10 wt% of the total mass of the alkylene oxide.

[0070] In the present application, the self-made double metal cyanide catalyst is used to catalyze the reaction of low-carbon alcohol with ethylene oxide and / or 1,2-propylene oxide, to prepare low-carbon alcohol block / random polyether, the required reaction temperature is lower, effectively solving the adverse effects of the low boiling point of the low-carbon alcohol starter on the reaction, reducing the free alcohol content in the product, and the product has a narrow molecular weight distribution. At the same time, since the double metal cyanide catalyst does not generate water, there is no need for dehydration treatment in the pretreatment process, avoiding the loss of low-carbon alcohol starter.

[0071] In the present application, the conversion rate of the synthesized low-carbon alcohol block / random polyether is high compared with conventional JFC penetrant products, and the content of by-product polyethylene glycol is low. The product has strong permeability and excellent permeability and emulsification properties.

[0072] The present application will be described in detail below through examples, but the scope of protection of the present application is not limited to this. In the following examples, if not specifically stated, the raw materials used are common commercially available products.

[0073] Example 1

[0074] Preparation process of double metal cyanide catalyst:

[0075] In a flask, 13.6 g of ZnCl2, 16.5 g of K3[Fe(CN)6] and 100 mL of deionized water were added to form a solution, wherein the molar ratio of Zn element in ZnCl2 to Fe element in K3[Fe(CN)6] was 2:1, then 2 g of phenyl boronic acid polyether ester was added, the amount of phenyl boronic acid polyether ester was 14.7 wt% of the mass of ZnCl2, and 0.5 g of comb-shaped copolymer DSP dispersant was added and stirred uniformly, the amount of comb-shaped copolymer DSP was 3.7 wt% of the mass of ZnCl2. Then the above obtained mixture was stirred and reacted at 50°C under inert atmosphere for 2h, and then was left to stand for 1h, to obtain a DMC precursor slurry, and the precursor slurry was filtered under reduced pressure to obtain a precipitate. The precipitate was washed with 100 mL of deionized water and tert-butyl alcohol for three times, and finally was dried in a vacuum drying oven at 60°C until the weight was constant, to obtain a high-activity catalyst (DMC-P1).

[0076] Preparation process of low-carbon fatty alcohol polyether:

[0077] 250 g of n-hexanol (mass fraction 99.5%), 8 mg of DMC-P1 catalyst and 1 mg of KOH were mixed and introduced into a 1L high-pressure reaction kettle equipped with a mechanical stirrer, a thermometer and a condenser, and were replaced with nitrogen three times and vacuumized, wherein the content of the DMC-P1 catalyst was 32 ppm based on the total weight of n-hexanol and DMC-P1 catalyst. The temperature was raised to 80°C, 20 g of 1,2-epoxypropane was introduced for induction reaction, and the pressure in the reaction kettle was 0.18 MPa. The reaction was continued at 80°C, and when the pressure in the kettle was reduced to 0.05 MPa, it was considered that the induction reaction was completed. Then 122 g of 1,2-epoxypropane was introduced, followed by the introduction of 431 g of ethylene oxide, and the pressure in the kettle was maintained at 0.25 MPa and the temperature was maintained at 90°C. After the introduction of the total amount of ethylene oxide and 1,2-epoxypropane was completed, the reaction was continued at 90°C, and when the pressure in the kettle was reduced to 0.03 MPa and the pressure in the system remained unchanged within 30 min, the reaction was completed, and the mass ratio of the total amount of ethylene oxide and 1,2-epoxypropane to n-hexanol was 2.3:1. When the temperature of the system decreased to room temperature, the reaction kettle was opened and the material was discharged, to obtain a hexanol block polyether product (C6Z-Q14).

[0078] Example 2

[0079] Preparation process of double metal cyanide catalyst:

[0080] In a flask, 12.5 g of NiCl2, 5.2 g of K3[Co(CN)6] and 40 mL of deionized water were added to form a solution, wherein the molar ratio of Ni element in NiCl2 to Co element in K3[Co(CN)6] was 6.1:1, then 2.75 g of polyvinylimidazole was added, the amount of polyvinylimidazole was 22 wt% of the mass of NiCl2, and 0.6 g of 18-crown-6 dispersant was added and stirred uniformly, the amount of 18-crown-6 was 4.8 wt% of the mass of NiCl2. Then the above obtained mixture was stirred and reacted at 50°C for 2h in an inert atmosphere, and then was left to stand for 1h to obtain a DMC precursor slurry. The precursor slurry was filtered under reduced pressure to obtain a precipitate. The precipitate was washed with 200 mL of deionized water and imidazole-based ionic liquid three times, and finally was dried in a vacuum drying oven at 60°C until the weight was constant, thereby obtaining a high-activity catalyst (DMC-P2).

[0081] Preparation process of low-carbon fatty alcohol polyether:

[0082] 250 g of n-heptanol (mass fraction 99.6%), 10 mg of DMC-P2 catalyst and 1.2 mg of NaHCO3 were mixed and introduced into a 1L high-pressure reaction kettle equipped with a mechanical stirrer, a thermometer and a condenser, and were replaced with nitrogen three times and vacuumized, wherein the content of the DMC-P2 catalyst was 40 ppm based on the total weight of n-heptanol and the DMC-P2 catalyst. The temperature was raised to 80°C, and 10 g of 1,2-epoxypropane and 15 g of ethylene oxide were introduced for induction reaction, and the pressure in the reaction kettle was 0.2 MPa. The induction reaction was considered to be completed when the temperature was kept at 90°C and the pressure in the kettle was reduced to 0.05 MPa. Then 101 g of 1,2-epoxypropane and 408 g of ethylene oxide were continuously introduced, and the pressure in the kettle was kept at 0.28 MPa and the temperature was kept at 90°C. After the total amount of ethylene oxide and 1,2-epoxypropane was added, the reaction was continued at 90°C, and the reaction was considered to be completed when the pressure in the kettle was reduced to 0.03 MPa and the pressure in the system remained unchanged within 30 min, and the mass ratio of the total amount of ethylene oxide and 1,2-epoxypropane to n-heptanol was 2.14:1. When the temperature of the system decreased to room temperature, the reaction kettle was opened and the material was discharged, thereby obtaining a heptanol random polyether product (C7Z-W15).

[0083] Example 3

[0084] Preparation process of double-metal cyanide catalyst:

[0085] In a flask, 6.5 g of ZnCl2, 5.8 g of NiCl2, 5.12 g of K3[Co(CN)6] and 40 mL of deionized water were added to form a solution, wherein the total moles of Zn element in ZnCl2and Ni element in NiCl2to the moles of Co element in K3[Co(CN)6] were 6.0:1, then 2.1 g of cis-norbornene bridged Salen-Ti was added, the amount of cis-norbornene bridged Salen-Ti was 17wt% of the total mass of ZnCl2and NiCl2, and 0.52 g of P123 dispersant was added and stirred uniformly, the amount of P123 was 4.2wt% of the total mass of ZnCl2and NiCl2. Then the above obtained mixture was stirred at 80℃ under inert atmosphere for 1.5h, and then was left to stand for 1h to obtain a DMC precursor slurry, and the precursor slurry was filtered under reduced pressure to obtain a precipitate. The precipitate was washed with 200 mL of deionized water and imidazole-based ionic liquid three times, and finally was dried in a vacuum drying oven at 60℃ until the weight was constant, to obtain a high-activity catalyst (DMC-P3).

[0086] Preparation process of low-carbon fatty alcohol polyether:

[0087] 200g of heptanol (n / i ratio 3.9), 8mg of DMC-P3 catalyst and 1mg of NaHCO3 were mixed and introduced into a 1L high-pressure reaction kettle equipped with a mechanical stirrer, a thermometer and a condenser, and replaced with nitrogen three times and vacuumized, wherein the content of the DMC-P3 catalyst was 40ppm based on the total weight of heptanol and DMC-P3 catalyst. The temperature was raised to 90℃, 15g of 1,2-epoxypropane was introduced for induction reaction, and the pressure in the reaction kettle was 0.18MPa. The reaction was maintained at 90℃, and when the pressure in the kettle was reduced to 0.05MPa, it was considered that the induction reaction was completed. Then 166g of 1,2-epoxypropane was introduced, followed by the introduction of 338g of ethylene oxide, and the pressure in the kettle was maintained at 0.25MPa and the temperature was maintained at 100℃. After the introduction of the total amount of ethylene oxide and 1,2-epoxypropane was completed, the reaction was continued at 100℃, and when the pressure in the kettle was reduced to 0.03MPa and the pressure in the system remained unchanged within 30min, the reaction was completed, and the mass ratio of the total amount of ethylene oxide and 1,2-epoxypropane to heptanol was 2.6:1. When the temperature of the system decreased to room temperature, the reaction kettle was opened and the material was discharged, to obtain a heptanol block polyether product (C7Y-Q25).

[0088] Example 4

[0089] The catalyst DMC-P3 was prepared according to the method of Example 3.

[0090] Preparation process of double metal cyanide catalyst:

[0091] In a flask, 6.5 g of ZnCl2, 5.8 g of NiCl2, 5.12 g of K3[Co(CN)6] and 40 mL of deionized water were added to form a solution, wherein the total moles of Zn element in ZnCl2and Ni element in NiCl2to the moles of Co element in K3[Co(CN)6] were 6.0:1, then 2.1 g of cis-norbornene bridged Salen-Ti was added, the amount of cis-norbornene bridged Salen-Ti was 17wt% of the total mass of ZnCl2and NiCl2, and 0.52 g of P123 dispersant was added and stirred uniformly, the amount of P123 was 4.2wt% of the total mass of ZnCl2and NiCl2. Then the above obtained mixture was stirred at 80℃ under inert atmosphere for 1.5h, and then was left for 1h to obtain a DMC precursor slurry. The precursor slurry was filtered under reduced pressure to obtain a precipitate. The precipitate was washed with 200 mL of deionized water and imidazole-based ionic liquid three times, and finally was dried in a vacuum drying oven at 60℃ until the weight was constant, to obtain a high-activity catalyst (DMC-P3).

[0092] Preparation process of low-carbon fatty alcohol polyether:

[0093] 200g of octanol (n / i ratio 4.5), 10mg of DMC-P3 catalyst and 1.2mg of Na2CO3 were mixed and introduced into a 1L high-pressure reaction kettle equipped with a mechanical stirrer, a thermometer and a condenser, and replaced with nitrogen three times and vacuumized, wherein the content of the DMC-P3 catalyst was 50ppm based on the total weight of the octanol and the DMC-P3 catalyst. The temperature was raised to 100℃, and 8g of 1,2-epoxypropane and 10g of ethylene oxide were introduced for induction reaction, and the pressure in the reaction kettle was 0.18MPa. The induction reaction was considered to be completed when the pressure in the kettle was reduced to 0.05MPa while keeping the temperature at 100℃. Then 81g of 1,2-epoxypropane and 396g of ethylene oxide were continuously introduced, and the pressure in the kettle was kept at 0.30MPa and the temperature was kept at 110℃. After the addition of the total amount of ethylene oxide and 1,2-epoxypropane was completed, the reaction was continued at 110℃, and the reaction was considered to be completed when the pressure in the kettle was reduced to 0.03MPa and the pressure in the system remained unchanged within 30min, and the mass ratio of the total amount of ethylene oxide and 1,2-epoxypropane to octanol was 2.48:1. When the temperature of the system decreased to room temperature, the reaction kettle was opened and the material was discharged, to obtain an octanol random polyether product (C8Y-W16).

[0094] Example 5

[0095] Preparation process of double metal cyanide catalyst:

[0096] In a flask, 16.1 g of ZnSO4, 16.5 g of K3[Fe(CN)6] and 100 mL of deionized water were added to form a solution, wherein the molar ratio of Zn element in ZnSO4 to Fe element in K3[Fe(CN)6] was 2:1, then 2 g of phenyl boronic acid polyether ester was added, the amount of phenyl boronic acid polyether ester was 12.4 wt% of the mass of ZnCl, and 0.5 g of comb-shaped copolymer DSP dispersant was added and stirred uniformly, the amount of comb-shaped copolymer DSP was 3.1 wt% of the mass of ZnCl. Then the above obtained mixture was stirred and reacted at 50°C under inert atmosphere for 2h, and then was left to stand for 1h, to obtain a DMC precursor slurry, and the precursor slurry was filtered under reduced pressure to obtain a precipitate. The precipitate was washed with 100 mL of deionized water and tert-butyl alcohol three times, and finally was dried in a vacuum drying oven at 60°C until the weight was constant, to obtain a high-activity catalyst (DMC-P4).

[0097] Preparation process of low-carbon fatty alcohol polyether:

[0098] 250 g of n-hexanol (mass fraction 99.5%), 8 mg of DMC-P4 catalyst and 1 mg of KOH were mixed and introduced into a 1L high-pressure reaction kettle equipped with a mechanical stirrer, a thermometer and a condenser, and were replaced with nitrogen three times and vacuumized, wherein the content of the DMC-P4 catalyst was 32 ppm based on the total weight of n-hexanol and DMC-P4 catalyst. The temperature was raised to 80°C, 20 g of 1,2-epoxypropane was introduced for induction reaction, and the pressure in the reaction kettle was 0.18 MPa. The reaction was continued at 80°C, and when the pressure in the kettle was reduced to 0.05 MPa, it was considered that the induction reaction was completed. Then 122 g of 1,2-epoxypropane was introduced, followed by the introduction of 431 g of ethylene oxide, and the pressure in the kettle was maintained at 0.25 MPa and the temperature was maintained at 90°C. After the introduction of the total amount of ethylene oxide and 1,2-epoxypropane was completed, the reaction was continued at 90°C, and when the pressure in the kettle was reduced to 0.03 MPa and the pressure in the system remained unchanged within 30 min, the reaction was completed, and the mass ratio of the total amount of ethylene oxide and 1,2-epoxypropane to n-hexanol was 2.3:1. When the temperature of the system decreased to room temperature, the reaction kettle was opened and the material was discharged, to obtain a hexanol block polyether product (C6Z-Q14-2).

[0099] Example 6

[0100] Preparation process of double metal cyanide catalyst:

[0101] In a flask, 13.6 g of ZnCl2, 16.1 g of K3[Cr(CN)6] and 100 mL of deionized water were added to form a solution, wherein the molar ratio of Zn element in ZnCl2 to Fe element in K3[Cr(CN)6] was 2:1, then 2 g of phenyl boronic acid polyether ester was added, the amount of phenyl boronic acid polyether ester was 14.7 wt% of the mass of ZnCl2, and 0.5 g of comb-shaped copolymer DSP dispersant was added and stirred uniformly, the amount of comb-shaped copolymer DSP was 3.7 wt% of the mass of ZnCl2. Then the above obtained mixture was stirred and reacted at 50°C under inert atmosphere for 2h, and then was left to stand for 1h, to obtain a DMC precursor slurry, and the precursor slurry was filtered under reduced pressure to obtain a precipitate. The precipitate was washed with 100 mL of deionized water and tert-butyl alcohol for three times, and finally was dried in a vacuum drying oven at 60°C until the weight was constant, to obtain a high-activity catalyst (DMC-P5).

[0102] Preparation process of low-carbon fatty alcohol polyether:

[0103] 250 g of n-hexanol (mass fraction 99.5%), 8 mg of DMC-P5 catalyst and 1 mg of KOH were mixed and introduced into a 1L high-pressure reaction kettle equipped with a mechanical stirrer, a thermometer and a condenser, and were replaced with nitrogen three times and vacuumized, wherein the content of the DMC-P5 catalyst was 32 ppm based on the total weight of n-hexanol and DMC-P5 catalyst. The temperature was raised to 80°C, 20 g of 1,2-epoxypropane was introduced for induction reaction, and the pressure in the reaction kettle was 0.18 MPa. The reaction was continued at 80°C, and when the pressure in the kettle was reduced to 0.05 MPa, it was considered that the induction reaction was completed. Then 122 g of 1,2-epoxypropane was introduced, followed by the introduction of 431 g of ethylene oxide, and the pressure in the kettle was maintained at 0.25 MPa and the temperature was maintained at 90°C. After the introduction of the total amount of ethylene oxide and 1,2-epoxypropane was completed, the reaction was continued at 90°C, and when the pressure in the kettle was reduced to 0.03 MPa and the pressure in the system remained unchanged within 30 min, the reaction was completed, and the mass ratio of the total amount of ethylene oxide and 1,2-epoxypropane to n-hexanol was 2.3:1. When the temperature of the system decreased to room temperature, the reaction kettle was opened and the material was discharged, to obtain a hexanol block polyether product (C6Z-Q14-3).

[0104] Example 7

[0105] Preparation process of double metal cyanide catalyst:

[0106] In a flask, 13.6 g of ZnCl2, 16.5 g of K3[Fe(CN)6] and 100 mL of deionized water were added to form a solution, wherein the molar ratio of Zn element in ZnCl2 to Fe element in K3[Fe(CN)6] was 2:1, then 2 g of phenyl boronic acid polyether ester was added, the amount of phenyl boronic acid polyether ester was 14.7 wt% of the mass of ZnCl2, and 0.5 g of comb-shaped copolymer DSP dispersant was added and stirred uniformly, the amount of comb-shaped copolymer DSP was 3.7 wt% of the mass of ZnCl2. Then the above obtained mixture was stirred and reacted at 100°C under inert atmosphere for 2h, and then was left to stand for 1h to obtain a DMC precursor slurry. The precursor slurry was filtered under reduced pressure to obtain a precipitate. The precipitate was washed with 100 mL of deionized water and tert-butyl alcohol for three times, and finally was dried in a vacuum drying oven at 60°C until the weight was constant, thereby obtaining a high-activity catalyst (DMC-P6).

[0107] Preparation process of low-carbon fatty alcohol polyether:

[0108] 250 g of n-hexanol (mass fraction 99.5%), 8 mg of DMC-P6 catalyst and 1 mg of KOH were mixed and introduced into a 1L high-pressure reaction kettle equipped with a mechanical stirrer, a thermometer and a condenser, and were replaced with nitrogen three times and vacuumized, wherein the content of the DMC-P6 catalyst was 32 ppm based on the total weight of the n-hexanol and the DMC-P6 catalyst. The temperature was raised to 80°C, 20 g of 1,2-epoxypropane was introduced for induction reaction, and the pressure in the reaction kettle was 0.18 MPa. The reaction was continued at 80°C, and when the pressure in the kettle was reduced to 0.05 MPa, it was considered that the induction reaction was completed. Then 122 g of 1,2-epoxypropane was introduced, followed by the introduction of 431 g of ethylene oxide, and the pressure in the kettle was maintained at 0.25 MPa and the temperature was maintained at 90°C. After the introduction of the total amount of ethylene oxide and 1,2-epoxypropane was completed, the reaction was continued at 90°C, and when the pressure in the kettle was reduced to 0.03 MPa and the pressure in the system remained unchanged within 30 min, the reaction was completed. The mass ratio of the total amount of ethylene oxide and 1,2-epoxypropane to n-hexanol was 2.3:1. When the temperature of the system decreased to room temperature, the reaction kettle was opened and the material was discharged, thereby obtaining a hexanol block polyether product (C6Z-Q14-4).

[0109] Comparative Example 1

[0110] The method of Example 7 was followed, except that no promoter was added in the preparation process of the low-carbon fatty alcohol polyether.

[0111] Preparation process of double metal cyanide catalyst:

[0112] In a flask, 13.6 g of ZnCl2, 16.5 g of K3[Fe(CN)6] and 100 mL of deionized water were added to form a solution, wherein the molar ratio of Zn element in ZnCl2 to Fe element in K3[Fe(CN)6] was 2:1, then 2 g of phenyl boronic acid polyether ester was added, the amount of phenyl boronic acid polyether ester was 14.7 wt% of the mass of ZnCl2, and then 0.5 g of comb-shaped copolymer DSP dispersant was added and stirred uniformly, the amount of comb-shaped copolymer DSP was 3.7 wt% of the mass of ZnCl2. Then the above obtained mixture was stirred and reacted at 100°C under inert atmosphere for 2h, and then was left to stand for 1h to obtain a DMC precursor slurry. The precursor slurry was filtered under reduced pressure to obtain a precipitate. The precipitate was washed with 100 mL of deionized water and tert-butyl alcohol three times, and finally was dried in a vacuum drying oven at 60°C until the weight was constant, thereby obtaining a high-activity catalyst (DMC-P6).

[0113] Preparation process of low-carbon fatty alcohol polyether:

[0114] 250 g of n-hexanol (mass fraction 99.5%) and 8 mg of DMC-P6 catalyst were mixed and introduced into a 1L high-pressure reaction kettle equipped with a mechanical stirrer, a thermometer and a condenser. Nitrogen was replaced three times and vacuum was applied. The content of the DMC-P6 catalyst was 32 ppm based on the total weight of n-hexanol and DMC-P6 catalyst. The temperature was raised to 80°C, 20 g of 1,2-epoxypropane was introduced for induction reaction, and the pressure in the reaction kettle was 0.18 MPa. The reaction was continued at 80°C, and when the pressure in the kettle decreased to 0.05 MPa, it was considered that the induction reaction was completed. Then 122 g of 1,2-epoxypropane was introduced, followed by the introduction of 431 g of ethylene oxide, and the pressure in the kettle was maintained at 0.25 MPa and the temperature was maintained at 90°C. After the introduction of the total amount of ethylene oxide and 1,2-epoxypropane was completed, the reaction was continued at 90°C, and when the pressure in the kettle decreased to 0.03 MPa and the pressure in the system remained unchanged within 30 min, the reaction was completed. The mass ratio of the total amount of ethylene oxide and 1,2-epoxypropane to n-hexanol was 2.3:1. When the temperature of the system decreased to room temperature, the reaction kettle was opened and the material was discharged, thereby obtaining a hexanol block polyether product (C6Z-Q14-D).

[0115] Test Example 1

[0116] The catalysts prepared in the test examples and comparative examples were used to prepare low-carbon fatty alcohol polyether, and the catalytic activity, free alcohol content and polyethylene glycol content of the low-carbon fatty alcohol polyether product were tested. The results are shown in Table 1.

[0117] The test method for catalytic activity was to record the mass change rate of alkylene oxide during the experiment, and the mass change rate of alkylene oxide represented the catalytic activity of the catalyst. The greater the mass change rate of alkylene oxide, the greater the catalytic activity of the catalyst;

[0118] The free alcohol content in the low-carbon fatty alcohol polyether product is determined by gas chromatography.

[0119] The polyethylene glycol content is determined by liquid chromatography.

[0120] The bimetallic catalyst in Table 1 is a commercially available product with a specification of DMC.

[0121] Comparison of catalyst performance in Table 1

[0122]

[0123]

[0124] As can be seen from the data in Table 1, the catalyst prepared by the technical solution of the embodiments of the present application has high activity for synthesizing low-carbon fatty alcohol polyether, and the free alcohol content and the polyethylene glycol content in the low-carbon fatty alcohol polyether product are low.

[0125] Test Example 2

[0126] Comparison of the performance of the fatty alcohol polyether prepared in the examples and comparative examples with commercially available products.

[0127] Wetting performance

[0128] Determination method: refer to the national standard GB / T 11983-2008 “Determination of wetting power of surfactants by immersion method”, and the wetting performance of 1.5 g / L surfactant solution is compared by immersion method. The wetting ability is inversely proportional to the length of wetting time. The test results are shown in Table 2 below.

[0129] Table 2 Comparison of wetting performance of fatty alcohol polyether products

[0130]

[0131]

[0132] As can be seen from Table 2, the bimetallic cyanide catalyst prepared by the method described in the present application for preparing low-carbon alcohol block / random polyether has excellent wetting and penetration performance.

[0133] Sample JFC-S in Table 2 is a natural C8-10 fatty alcohol ether with an EO addition number of 4-6; JFC-C is a synthetic C8-10 alcohol ether with an EO addition number of 4-5.

[0134] Capillary effect

[0135] Test method: refer to the industry standard FZ / T 01071-2008 "Textile Capillary Effect Test Method" test. The cotton cloth strip is cut into 3cm*30cm, treated with 1g / L surfactant solution at 90℃ for 30min, and then dried. A parallel line is made at 1cm from one end of the cloth strip, and the other end is fixed with a stand to make it hang vertically, with the lower end immersed in 5g / L potassium dichromate solution, so that the liquid surface is flush with the parallel line. The height of the potassium dichromate wetting along the cotton cloth strip is recorded at 5min and 30min. The test results are shown in Table 3 below.

[0136] Table 3 Comparison of capillary effect of fatty alcohol polyether products

[0137]

[0138]

[0139] The product of the present application shows better wetting and penetration performance than the existing commercially available JFC product in terms of wetting and capillary effect. Therefore, it can be considered that the preparation and application method of a double metal cyanide (DMC) catalyst for the synthesis of low-carbon fatty alcohol block / random polyether provided by the present application has good application effect.

[0140] It should be understood that parts not elaborated in the specification are all prior art.

[0141] The preferred embodiments of the present application are described in detail above, but the present application is not limited thereto. Within the technical concept of the present application, various simple modifications can be made to the technical solutions of the present application, including the combination of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as disclosed by the present application and fall within the protection scope of the present application.

Claims

1. A process for the preparation of a double metal cyanide catalyst, characterized in that The method comprises mixing a soluble transition metal salt, a cyanometallic salt, a reaction medium and a dispersant, and then performing a reaction under an inert atmosphere; wherein the cyanometallic salt is K3[M(CN)6], wherein metal M is selected from at least one of Co, Fe and Cr.

2. The method of claim 1, wherein, The soluble transition metal salt is a zinc salt and / or a nickel salt, preferably at least one of zinc chloride, zinc sulfate and nickel chloride.

3. The method according to claim 1 or 2, characterized in that, The molar ratio of the amount of the soluble transition metal salt to the amount of the cyanometallic salt is (1.0-10):1, wherein the soluble transition metal salt is calculated based on the transition metal element, and the cyanometallic salt is calculated based on the metal M element; When the metal M is Co, the molar ratio of the amount of the soluble transition metal salt to the amount of the cyanometallic salt is (1.5-10):1, preferably (5.5-6.1):1, wherein the soluble transition metal salt is calculated based on the transition metal element, and the cyanometallic salt is calculated based on the metal Co element; When the metal M is Fe, the molar ratio of the amount of the soluble transition metal salt to the amount of the cyanometallic salt is (1.5-2.5):1, preferably (1.8-2.2):1, wherein the soluble transition metal salt is calculated based on the transition metal element, and the cyanometallic salt is calculated based on the metal Fe element; When the metal M is Cr, the molar ratio of the amount of the soluble transition metal salt to the amount of the cyanometallic salt is (1.0-3.5):1, preferably (2.1-3.2):1, wherein the soluble transition metal salt is calculated based on the transition metal element, and the cyanometallic salt is calculated based on the metal Cr element.

4. The method according to claim 1 or 2, characterized in that, The reaction medium is selected from at least one of a borate compound, a cage polydentate ligand, a polyionic liquid and a chiral bis-Salen ligand, preferably at least one of a phenyl boronic acid polyether ester, an adamantane polycarboxylic acid, a polyvinylimidazole and a cis-norbornene bridged Salen-Ti; The amount of the reaction medium is 10-30 wt%, preferably 15-25 wt%, of the mass of the soluble transition metal salt.

5. The method of claim 1, wherein, The dispersant is selected from at least one of a polyethylene glycol, a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, a polytetrahydrofuran, 18-crown-6 ether and a comb copolymer DSP; The amount of the dispersant is 0.5-5 wt%, preferably 3-5 wt%, of the mass of the soluble transition metal salt.

6. The method of claim 1 or 2, wherein, The reaction conditions include a reaction temperature of 35-105°C, preferably 50-80°C, and a reaction time of 0.5-24 h, preferably 1.5-2 h.

7. The method of claim 1, wherein, The method further comprises, after the reaction under the inert atmosphere, standing, filtering the obtained precursor slurry, and washing and drying the obtained solid product.

8. A double metal cyanide catalyst prepared by the method of any one of claims 1-7.

9. A process for the preparation of a low carbon fatty alcohol polyether, characterized in that the process comprises: The low-carbon fatty alcohol initiator, the double metal cyanide catalyst, the cocatalyst and the alkylene oxide are reacted; The low-carbon fatty alcohol initiator has 6-10 carbon atoms; The low-carbon fatty alcohol initiator has 6-10 carbon atoms; The double metal cyanide catalyst is a double metal cyanide catalyst prepared by the method of any one of claims 1-7 or the double metal cyanide catalyst of claim 8.

10. The method of claim 9, wherein, The low-carbon fatty alcohol initiator is a saturated alkyl alcohol with 6-8 carbon atoms; And / or, the co-catalyst is at least one selected from KOH, NaOH, NaHCO3 and Na2CO3; And / or, the alkylene oxide is ethylene oxide and / or 1,2-propylene oxide.

11. The method according to claim 9 or 10, characterized in that, The content of the double metal cyanide catalyst is 20-100 ppm, preferably 20-50 ppm, based on the total weight of the low-carbon fatty alcohol initiator and the double metal cyanide catalyst; And / or, the amount of the co-catalyst is 5-20 wt%, preferably 8-15 wt%, of the mass of the double metal cyanide catalyst; And / or, the mass ratio of the alkylene oxide to the low-carbon fatty alcohol initiator is (1.1-2.7):

1.

12. The method of claim 9, wherein, The process of reacting the low-carbon fatty alcohol initiator, the double metal cyanide catalyst, the co-catalyst and the alkylene oxide comprises mixing the low-carbon fatty alcohol initiator, the double metal cyanide catalyst and the co-catalyst, then adding part of the alkylene oxide for an induction reaction, and then adding the remaining part of the alkylene oxide for a subsequent reaction.

13. The method of claim 12, wherein, The temperature of the induction reaction is 8-12℃ lower than the temperature of the subsequent reaction; And / or, the temperature of the induction reaction is 60-110℃, preferably 80-100℃; and the temperature of the subsequent reaction is 70-115℃; And / or, the initial system pressure of the induction reaction is 0.05-0.2 MPa; and the induction reaction ends when the system pressure is lower than 0.05 MPa; And / or, during the addition of the remaining part of the alkylene oxide, the system pressure is kept ≤0.3 MPa; and the subsequent reaction ends when the reaction is to a system pressure ≤0.03 MPa and the system pressure remains unchanged within 30 min after the addition of the remaining part of the alkylene oxide; And / or, the mass of the part of the alkylene oxide added in the induction reaction stage is 2-10 wt% of the total mass of the alkylene oxide.